Secure Computation Interfaces - Costa, Manuel; Rajamani, Sriram; Russinovich, Mark; Vaswani, Kapil; Hodson, Orion; Peinado, Marcus (Microsoft, 2015)
Applications such as Secure Hadoop need to have part of their data and code isolated from privileged software (e.g., the operating system), and they need to be able to establish secure communication channels between the isolated code and remote machines. This document investigates the APIs needed to develop these applications.